Analysing Critical Success Factors for Supporting On-line - Varela, Leonilde (2018)
On-line shopping is nowadays is a highly frequent action but there are several critical factors that have to be considered for enabling websites and platforms to be able to offer all necessary requisites for guaranteeing user friendly, secure and also enjoyable shopping experiences to clients, offering them exactly what they expect to buy, and quickly find, among a huge offer available on-line. In this paper a set of considered critical success factors are analysed on a set of top ranked websites, about luxurious furniture, to understand to what extent these critical factors are satisfied. The results can be taken into consideration for implementing a successful businesses through e-commerce from herein analysed perspectives.